BTS Universe: um estudo do espaço associado em uma narrativa transmídia - Aisawa, Karen Naomi (Universidade Federal de São Carlos, 2021)
This study aims to investigate the relationships between canonic space and associate space in the editorial object BTS Universe (BU), a serialized fictional narrative authored by the South Korean pop group BTS along with the company that manages it, Big Hit Music. Ongoing since 2015, the plot is composed by a series of materials of different discursive genres and spread across different platforms (whether online or not), characterizing what we take as transmedia storytelling (JENKINS, 2015), that is, a multi-platform narrative of an expanded and dispersed character, and that entails the engagement of a broad community producing derivative content that is incorporated into the plot, complexifying it. These constitutive objects of the narrative circulate in various platforms, such as YouTube and Twitter, for example, and are fragments of the complete story, which can only be glimpsed in its entirety from a relationship of co-enunciation with the “reader”, that is, with the fandom ARMY, responsible for the effective collection and (re)organization of these fragments, a process that is formalized and made public through the production of derived editorial objects that take on diverse discursive genres and circulate in platforms that are also diverse, such as YouTube videos, comments on social networks, texts in blogs, etc. Furthermore, the BU also incorporates in its narrative elements and references to works that escape its authorship, such as the work Demian, by Hermann Hesse, who inspired the creation of one of the Eras of the story. Considering the scenario outlined, we seek to understand with this study how the constitution of the canonic space and the associate space of this plural object occurs, which puts into question the notion of work, crucial to several fields of knowledge, given that, as we will see throughout the study, work is not only the intellectual work of an author, but it is also the technique, the inscriptional materiality and, above all, the recognition by a network of apparatus of a discursive field. In addition, other background issues guide the conduct of this research, such as the characterization of BTS Universe as a work of digital literature or as entertainment, or the reflection on the constitution of different associate spaces for fans of distinctive languages, or even the observation of the creation of associate spaces that create other associate spaces when they gain relevance, among others. Thus, we mobilized for this study the theoretical-methodological framework proposed by Maingueneau (2006), allied to the foundations of mediology thought by Debray (1991; 2000), to study two materials authored by the group/company, three works authored by third parties, referenced less or more directly in the narrative, and four theories authored by fans, aiming at the analysis of materials of each of the constitutive authors of this transmedia storytelling.
BTS Universe: a study of the associate space in a transmedia storytelling
Keywords: Análise do discurso; BTS Universe; Espaço associado; Midiologia; Narrativa transmídia; Discourse analysis; Associate space; Mediology; Transmedia storytelling; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA